Analysis of Sustainable Competitive Advantage Strategies in Embroidery Industry Centers in Tasikmalaya - Hanafi, Mohamad; Fauziyah, Azizah; Nurfitriya, Mira (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The embroidery industry in Tasikmalaya is one of the creative economic sectors with significant potential for growth. However, facing increasingly intense competition requires effective strategies to maintain and enhance competitive advantage. This research aims to identify competitive advantages and the VRIO Framework in the embroidery industry in Tasikmalaya, as well as to develop strategies for sustainable competitive advantage within the embroidery industry centers in Tasikmalaya. The VRIO Framework is used to evaluate a company's resources and capabilities based on four criteria: Value, Rarity, Imitability, and Organization. The object of this research is the embroidery industry centers in Tasikmalaya. The research method used is quantitative with a descriptive approach, where data is collected through observation, questionnaires, and interviews structured. The types of data used are primary and secondary data. The tool used to formulate competitive advantage strategies is the VRIO framework. The results of this study indicate that the embroidery industry in Tasikmalaya has advantages in product uniqueness, competitive pricing, and difficulty to replace, and is positioned with a temporary competitive advantage and economic performance above normal.